2019
DOI: 10.1155/2019/4958294
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Regulating Gut Microbiota in Abdominal Obese Rats Induced by High-Fat Diet

Abstract: Objective. To investigate the effects of acupuncture on metabolic health and gut microbiota dysbiosis in diet-induced abdominal obese model. Materials and Methods. Male Sprague-Dawley rats were randomly distributed into normal chow diet (NCD) group and high-fat diet (HFD) group. After 12 weeks of HFD feeding, an abdominal obese rat model was established. The abdominal obese rats were further assigned to acupuncture group (n=7) and nontreated HFD group (n=7). Acupuncture was applied to bilateral GB 26 of rats f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 55 publications
(42 reference statements)
1
30
0
Order By: Relevance
“…The HFD feed was processed by the Animal Experimental Center of the Army Military Medical University. The HFD feed formula was: 60% of basic feed, 10% of lard (cooked), 5% of sucrose, 5% of whole milk powder, 8% of peanut, 10% of egg, and 2% of salt ( Chandler et al., 2005 ; Wang et al, 2019 ). The weight of the rats was monitored and recorded weekly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HFD feed was processed by the Animal Experimental Center of the Army Military Medical University. The HFD feed formula was: 60% of basic feed, 10% of lard (cooked), 5% of sucrose, 5% of whole milk powder, 8% of peanut, 10% of egg, and 2% of salt ( Chandler et al., 2005 ; Wang et al, 2019 ). The weight of the rats was monitored and recorded weekly.…”
Section: Methodsmentioning
confidence: 99%
“…The weight of the rats was monitored and recorded weekly. The criteria for selecting overweight and obese rats was to select HFD group rats who increased their body weight by 10% or 20%, respectively, compared to the average weight of the regular diet group ( Chandler et al., 2005 ; Wang et al, 2019 ). In our study, we selected 60 obese rats and 60 overweight rats.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have confirmed that acupuncture treatment has a good effect on relieving migraine attacks and digestive symptoms [ 33 , 34 ]. There is evidence that acupuncture can regulate gut microbiota disorders and improve the diversity and richness of bacteria species in the gut [ 35 , 36 ]. Several lines of research on the use of acupuncture and flunarizine for migraine have shown that flunarizine has a good effect in reducing pain intensity and improving quality of life, and in addition to the effects mentioned above, acupuncture can effectively reduce the number of migraine days and regulate psychological state [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HFD feed was processed by the Animal Experimental Center of the Army Military Medical University. The HFD feed formula was: 60% of basic feed, 10% of lard (cooked), 5% of sucrose, 5% of whole milk powder, 8% of peanut, 10% of egg, and 2% of salt (Chandler et al, 2005;Wang et al, 2019). The weight of the rats was monitored and recorded weekly.…”
Section: The Obesity Modelmentioning
confidence: 99%